A mycobacterial growth inhibition assay (MGIA) for bovine TB vaccine development. (September 2017) - Pepponi, Ilaria; Khatri, Bhagwati; Tanner, Rachel; Villarreal-Ramos, Bernardo; Vordermeier, Martin; McShane, Helen
Abstract: Human tuberculosis remains a significant cause of mortality and morbidity throughout the world. The global economic impact of bovine TB is considerable. An effective vaccine would be the most cost-effective way to control both epidemics, particularly in emerging economies. TB vaccine research would benefit from the identification of an immune correlate of protection with which vaccines could be gated at both preclinical and clinical levels. In-vitro mycobacterial growth inhibition assays (MGIA) are functional assays that include most aspects of the complex host immune response to mycobacteria, and they may serve as functional immune correlates for vaccine development. We applied to cattle an MGIA that was developed for use with human and murine samples. Several technical difficulties were encountered while transferring it to the cattle model. However, our data demonstrate that the assay was not discriminatory in cattle and further work is needed before using it for bovine TB vaccine development.